VARIABILITY IN GROWTH PARAMETERS OF RED FLESHED AND WHITE FLESHED GUAVA GENOTYPES - P. H. ULEMALE,; T. B. TAMBE, (The Bioscan, 2015)
The present investigation was carried out with object to study morpho-phenological characters of guava genotypes. The three year pooled data indicates that significant variation was found for this trait among the genotypes of guava. The highest height of plant (4.21 m), highest tree volume (55.32 m3) and highest leaf area (81.98 cm2) was recorded in genotype GRS4, whereas, lowest height of plant (2.60 m), tree volume (24.93 m3) was observed for genotype GWS8 and lowest leaf area (52.16 cm2) was recorded in genotype GRS1. The spreading to erect tree habit with medium to dense canopy was observed for all guava genotypes. Whereas, pale to dark green coloured leaves was recorded in most of genotypes. Leaf apex was obtuse in most of genotypes viz., GRS4, GWS5, GWS6, GWS7, GWS8 and L-49 and acute was in GRS1, GRS2 and GRS3.Whereas, Base of leaf was found round in all genotypes. Solitary type with white colour of flower was found in all genotypes viz., GRS1, GRS2, GRS3, GRS4, GWS5, GWS6, GWS7, GWS8, GWS9 and L-49.